2013
DOI: 10.1038/clpt.2013.200
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Targeted Therapy for Anaplastic Lymphoma Kinase–Rearranged Non–Small Cell Lung Cancer

Abstract: The identification of chromosomal rearrangements involving the anaplastic lymphoma kinase (ALK) gene in ~3-5% of non-small cell lung cancer (NSCLC) tissues and the demonstration that the first-in-class ALK tyrosine kinase inhibitor, crizotinib, can effectively target these tumors represent a significant advance in the evolution of personalized medicine for NSCLC. Single-arm studies demonstrating rapid and durable responses in the majority of ALK-positive NSCLC patients treated with crizotinib have been followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 88 publications
(137 reference statements)
0
53
0
1
Order By: Relevance
“…AP26113 is a novel TKI that potently inhibits mutant activated forms of the ALK and EGFR genes as well as TKI-resistant forms, including L1196M of the ALK gene and T790M of the EGFR gene (29). Preliminary data for an ongoing dose-finding phase I/II study of AP26113 for advanced malignancy refractory to standard treatment showed the efficacy and safety of the compound in patients with NSCLC previously treated with ALKi or EGFR-TKIs.…”
Section: Other Second-generation Alk Inhibitorsmentioning
confidence: 99%
“…AP26113 is a novel TKI that potently inhibits mutant activated forms of the ALK and EGFR genes as well as TKI-resistant forms, including L1196M of the ALK gene and T790M of the EGFR gene (29). Preliminary data for an ongoing dose-finding phase I/II study of AP26113 for advanced malignancy refractory to standard treatment showed the efficacy and safety of the compound in patients with NSCLC previously treated with ALKi or EGFR-TKIs.…”
Section: Other Second-generation Alk Inhibitorsmentioning
confidence: 99%
“…[20][21][22]. In contrast, crizotinib hardly inhibited RET (IC 50 ¼ 3,200 nmol/L) and LDK378, a second-generation ALK inhibitor (23,24), did not inhibit RET kinase activity (IC 50 , >5,000 nmol/L). In addition, ATPcompetitive binding assay showed that alectinib bound to RET at a dissociation constant (K D ) value of 7.6 nmol/L.…”
Section: Inhibition Of Ret Kinase Activity Mediated By Alectinibmentioning
confidence: 99%
“…[94][95][96][97][98][99][100][101][102][103][104] Ceritinib is an orally active TKI of ALK, which also inhibits the insulin-like growth factor 1 (IGF-1) receptor but not MET. An expanded phase I trial showed that ceritinib was very active in 122 patients with locally advanced or metastatic NSCLC who have ALK gene rearrangements.…”
Section: Alk Gene Rearrangementsmentioning
confidence: 99%